Effect of COVID-19 on Pet Food Bank Servicing: Quantifying Numbers of Clients Serviced in the Vancouver Downtown Eastside, British Columbia, Canada - Schor, Marina; Protopopova, Alexandra (Frontiers in Veterinary Science, 2021)
Previous research has focused on the benefits and difficulties of pet ownership in people, who are experiencing homelessness. However, many pet services, such as pet food banks, serve a more varied population of people. Furthermore, the effect of the COVID-19 pandemic has not been documented within the context of pet food banks. Vancouver’s Downtown Eastside (DTES) population comprises a notable proportion of the city’s overall population and has a high density of people who are experiencing financial hardships, but some of whom do not always experience homelessness. The purpose of this study was to gain an understanding of the number of clients and pets that are being serviced by a pet food bank, whether that has changed over time, and if it was impacted by the COVID-19 pandemic. We analysed available attendance and service records from The British Columbia Society for the Prevention of Cruelty to Animals pet food bank between 2013 and 2020. We found that a median of 100 clients attended the food bank each week and that most of the companion animals serviced were cats (72.5%), then followed by dogs (25.2%), and rats (1.2%). Servicing was not consistent over time, with a weekly pattern of decreased attendance every fourth week of the month, which coincided with income assistance payments. This suggests that either servicing needs are decreased with income assistance or that the week of the month may present an access to care challenge. We also observed a decrease in the clientele attending in 2020 compared to previous years, suggesting an effect of COVID-19. Specifically, this trend was present for cats, rats, rabbits, and “other”, but not for dog owners; the number of dog owners receiving services did not change in 2020, suggesting a difference between needed services in dog versus other pet owners. The yearly trends shed light on the impact of COVID-19 on vulnerable populations, highlighting the need for additional support through times of crisis. Overall, the data show a complex relationship between pet service provision and other community issues and highlight the need to consider pet food banks within the greater social services networks.